Uncertainty Reduction Through Social Media and Post-Concert Emotional Recovery Among K-Pop Fans - Jasmine Alya Pramesthi (CV. ITTC INDONESIA, 2026)
Post-Concert Depression (PCD), the emotional emptiness and mood decline experienced after intense concert euphoria remains an underexplored phenomenon in communication research, particularly regarding how fans manage this condition through communicative strategies. This study aims to examine the effect of uncertainty reduction strategies on the emotional well-being of K-Pop fans following concert attendance, specifically in the context of overcoming Post-Concert Depression (PCD). This study employed an explanatory sequential mixed methods design, combining quantitative and qualitative phases. In the quantitative phase, a survey was administered to 120 K-Pop fans who had attended at least one concert in 2024, selected using purposive sampling. Data were analyzed using simple linear regression with the assistance of SPSS 28. In the qualitative phase, in-depth interviews were conducted with five informants drawn from the survey respondents to deepen the quantitative findings Emotional well-being was operationalized using the Positive and Negative Affect Schedule (PANAS), measuring both positive and negative affect dimensions. The quantitative results reveal that uncertainty reduction (X) has a significant positive effect on emotional well-being (Y), explaining 49.5% of the variance (R² = 0.495; t = 10.761; p < 0.001). Interview findings corroborate these results, demonstrating that communication strategies, particularly active strategies such as peer interaction and information sharing, effectively alleviate PCD symptoms and enhance fans' post-concert emotional states. These findings contribute to the literature on the extended application of Uncertainty Reduction Theory beyond interpersonal contexts into the domain of popular culture and fan communication.